Cyberspaces, Data Analytics, and policing - Skillicorn, David (Boca Raton: CRC Press, Taylor & Francis, 2022)
"Cyberspace is changing the face of crime. For criminals it has become a place for rich collaboration and learning, not just within one country; and a place where new kinds of crimes can be carried out, and a vehicle for committing conventional crimes with unprecedented range, scale, and speed. Law enforcement faces a challenge in keeping up and dealing with this new environment. The news is not all bad - collecting and analyzing data about criminals and their activities can provide new levels of insight into what they are doing and how they are doing it. However, using data analytics requires a change of process and new skills that (so far) many law enforcement organizations have had difficulty leveraging. Cyberspace, Data Analytics, and Policing surveys the changes that cyberspace has brought to criminality and to policing with enough technical content to expose the issues and suggest ways in which law enforcement organizations can adapt"-- Provided by publisher.
Keywords: Computer Crimes -- Prevention; Criminal Justice, Administration of -- Computer Network Resources; Police -- Data Processing